(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Fulfilling tax obligations is an important aspect of a well-functioning economy, as it ensures that the government has the necessary resources to provide public goods and services. However, in many countries, including Uzbekistan, there are challenges associated with tax compliance. These challenges include a lack of awareness and education about tax obligations, complex and opaque tax laws and regulations, and a high level of informality in the economy.